2014
DOI: 10.3389/fncel.2014.00380
|View full text |Cite|
|
Sign up to set email alerts
|

Versatility of the complement system in neuroinflammation, neurodegeneration and brain homeostasis

Abstract: The immune response after brain injury is highly complex and involves both local and systemic events at the cellular and molecular level. It is associated to a dramatic over-activation of enzyme systems, the expression of proinflammatory genes and the activation/recruitment of immune cells. The complement system represents a powerful component of the innate immunity and is highly involved in the inflammatory response. Complement components are synthesized predominantly by the liver and circulate in the bloodst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 176 publications
(268 reference statements)
5
162
0
Order By: Relevance
“…Activation of the lectin pathway has been implicated in tissue damage associated with ischemia reperfusion of several organs and tissues including myocardium, gastrointestinal tract, skeletal muscles, and brain (27,28). The results of this study indicate that the lectin pathway activation is also involved in the adverse pregnancy outcome observed in DBA/2-mated CBA/J.…”
Section: Discussionmentioning
confidence: 59%
“…Activation of the lectin pathway has been implicated in tissue damage associated with ischemia reperfusion of several organs and tissues including myocardium, gastrointestinal tract, skeletal muscles, and brain (27,28). The results of this study indicate that the lectin pathway activation is also involved in the adverse pregnancy outcome observed in DBA/2-mated CBA/J.…”
Section: Discussionmentioning
confidence: 59%
“…The complement system mediates immune responses to inflammatory triggers to attract additional phagocytes, enhances the ability of phagocytic cells to clear microbes and damaged cells, and precipitates lysis of foreign microbes via the membrane attack complex (MAC) (Janeway, Travers et al 2001, Sarma and Ward, 2011). However, inappropriate complement activation can also cause cell injury or death and has been recognized as an important pathogenic factor in many diseases including neurodegenerative diseases such as AD (Crehan et al, 2012; Orsini et al, 2014). The gene expression of CFB and C3 were upregulated 266 and 12-fold, respectively, in the LPS/ IFNγ-activated microglial cells compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
“…In traumatic brain injury, it has been shown that the majority of complement proteins in the brain are from the periphery due to the dysfunction of the BBB [34]. A number of studies suggest mast cell activation as a mechanism for BBB disruption and brain inflammation in ASD [35,36]. However, further studies are warranted to better understand the brain versus peripheral contribution of the complement system in ASD.…”
Section: Discussionmentioning
confidence: 99%